2003
DOI: 10.1038/sj.jhh.1001514
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy and tolerability of the combination delapril plus indapamide in the treatment of mild to moderate essential hypertension: a randomised, multicentre, controlled study

Abstract: The aim of the study was to evaluate efficacy and tolerability of two different fixed combinations of an angiotensin-converting enzyme inhibitor and a diuretic: delapril+indapamide (D+I) and captopril+hydrochlor-othiazide (C+H) administered for 6 months to patients with mild to moderate essential hypertension. In all, 96 centres participated in this randomised, parallel groups, controlled study. A total of 829 patients with uncomplicated mild to moderate hypertension were randomised, and 790 were eligible for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Efficacy analyses [14][15][16][17] demonstrate the capacity of DϩI to significantly reduce SBP and DBP; in particular, the data of this study confirm the normalization rate (82.5%) and responder rate (92.5%) observed in previous controlled trials for DϩI. The results demonstrate a similar antihypertensive efficacy of both combinations and showed similar tolerability between treatments.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Efficacy analyses [14][15][16][17] demonstrate the capacity of DϩI to significantly reduce SBP and DBP; in particular, the data of this study confirm the normalization rate (82.5%) and responder rate (92.5%) observed in previous controlled trials for DϩI. The results demonstrate a similar antihypertensive efficacy of both combinations and showed similar tolerability between treatments.…”
Section: Discussionsupporting
confidence: 83%
“…Compared with thiazide diuretics, indapamide appears to have less potassiumdepleting activity, and, in long-term therapy, it induces no negative effect on lipid or glucose metabolism. [9][10][11] Clinical trials [12][13][14][15][16][17] of the combination of delapril plus indapamide (DϩI) showed, both in case of single administration and at steady state, no interaction between the 2 components, and demonstrated its antihypertensive efficacy. The efficacy of this combination therapy in comparative studies 15,16 was significantly higher than that of the single components and was superior to that of captopril plus hydrochlorothiazide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several such trials have been reported in the past few years [5][6][7][8]. The same mechanism is true for ARB + diuretic combinations [9][10][11][12].…”
Section: Angiotensin-inhibiting Drugs and Diureticsmentioning
confidence: 93%
“…Much has been written in recent years about the advantages and disadvantages of using fixed drug combinations [5][6][7][8][9][10][11]13,15,[17][18][19][20][21][22][23][24][25][26][27][28][29]. There are also arguments relevant to the proper timing of instituting a chosen fixed combination-that is, as first choice upon initiation of drug therapy or upon reaching the BP goal, after which no further changes are likely to be needed [31][32][33][34][35].…”
Section: Fixed Drug Combinationsmentioning
confidence: 99%